2016
DOI: 10.1111/dar.12475
|View full text |Cite
|
Sign up to set email alerts
|

The prominence of smoking‐related mortality among individuals with alcohol‐ or drug‐use disorders

Abstract: Given the current findings, addressing tobacco smoking among persons with substance-use disorders should be a critical concern, especially given the heavy smoking-related mortality burden and the currently limited attention devoted to smoking in these populations. [Callaghan RC, Gatley JM, Sykes J, Taylor L. The prominence of smoking-related mortality among individuals with alcohol- or drug-use disorders. Drug Alcohol Rev 2018;37:97-105].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
1
17
0
2
Order By: Relevance
“…Individuals in SUD treatment are more likely to die from tobacco-related diseases compared to the general population (Bandiera et al, 2015;Hurt et al, 1996). For example, (Callaghan et al, 2018) extracted discharge records for all patients hospitalized in California (1990California ( -2005 and matched them to death records. They found that among hospital discharges reporting drug or alcohol use disorders, 36-49% of all deaths were attributable to smoking-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals in SUD treatment are more likely to die from tobacco-related diseases compared to the general population (Bandiera et al, 2015;Hurt et al, 1996). For example, (Callaghan et al, 2018) extracted discharge records for all patients hospitalized in California (1990California ( -2005 and matched them to death records. They found that among hospital discharges reporting drug or alcohol use disorders, 36-49% of all deaths were attributable to smoking-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Further, those with opioid use disorder (OUD) had a significantly higher risk of mortality from all 19 tested smoking related conditions (i.e. cardiovascular, respiratory diseases and cancers) when compared to the general population ( Callaghan, Gatley, Sykes, & Taylor, 2018 ). The observed relationship between tobacco smoking and health among people with OUD is particularly concerning given the high prevalence of smoking in this population.…”
Section: Introductionmentioning
confidence: 99%
“…It is two to 13 times more prevalent in people with other substance use disorders (SUDs) than in control subjects [2], and SUD individuals present many risk factors for more severe patterns of tobacco smoking [3]. Consequently, tobaccorelated diseases may account for 36-49% deaths of people who ever received inpatient treatment for other SUDs [4].…”
Section: Introductionmentioning
confidence: 99%